2012
DOI: 10.1080/00438243.2012.646101
|View full text |Cite
|
Sign up to set email alerts
|

Flightless ducks, giant mice and pygmy mammoths: Late Quaternary extinctions on California's Channel Islands

Abstract: Explanations for the extinction of Late Quaternary megafauna are heavily debated, ranging from human overkill to climate change, disease and extraterrestrial impacts. Synthesis and analysis of Late Quaternary animal extinctions on California's Channel Islands suggest that, despite supporting Native American populations for some 13,000 years, few mammal, bird or other species are known to have gone extinct during the prehistoric human era, and most of these coexisted with humans for several millennia. Our analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…In addition, it is important to recognize that with post-glacial sea level rise in the latest Pleistocene/earliest Holocene, many potentially important archeological sites on the northern Channel Islands would now be submerged on what are presently the insular shelves (Clark et al, 2014;Reeder-Myers et al, 2015). Nevertheless, Rick et al (2012b) concluded that climate change and ecological disturbance were likely the main causes for mammoth extinction on the Channel Islands. These investigators also point out that with post-glacial sea level rise, one consequence Fig.…”
Section: Implications For Causes Of Mammoth Extinctionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is important to recognize that with post-glacial sea level rise in the latest Pleistocene/earliest Holocene, many potentially important archeological sites on the northern Channel Islands would now be submerged on what are presently the insular shelves (Clark et al, 2014;Reeder-Myers et al, 2015). Nevertheless, Rick et al (2012b) concluded that climate change and ecological disturbance were likely the main causes for mammoth extinction on the Channel Islands. These investigators also point out that with post-glacial sea level rise, one consequence Fig.…”
Section: Implications For Causes Of Mammoth Extinctionmentioning
confidence: 99%
“…With post-glacial warming, one could also add vegetation community change (Heusser, 1995(Heusser, , 2000 and alteration of freshwater sources as stressors on mammoth populations. An examination of the new evidence for mammoth antiquity on the Channel Islands, presented here, provides a partial test of the hypothesis presented by Rick et al (2012b) that mammoth extinction on the Channel Islands was due to climate change, ecological disturbance, and loss of land area. Given the findings reported here that mammoth remains are at least as old as~80 ka, it is possible to consider how glacial-interglacial climate and sea level change could have affected mammoths in the penultimate Quaternary climate cycle.…”
Section: Implications For Causes Of Mammoth Extinctionmentioning
confidence: 99%
See 1 more Smart Citation
“…the coastal plain habitat (Figs. 2 and 3) that would have been ideal for mammoths (Agenbroad et al, 2005;Rick et al, 2012). The Channel Islands contain few terrestrial mammals and the precise timing of the appearance of island gray foxes (Urocyon littoralis), island spotted skunks (Spilogale gracilis), and island deer mice (Peromyscus maniculatus) is the subject of considerable debate.…”
Section: Terrestrial Environmentsmentioning
confidence: 99%
“…Nagaoka and Allen (2009) draw on research in New Zealand, which shows a clear case of human influence on extinction, but also one where other processes lead to the decline in concert with other forces (habitat alteration, climate). The complex nature of island extinctions was also noted by Jones et al (2008) for the California Coast, suggesting that the extinction of the flightless duck (Chendytes lawi) was protracted and followed millennia of human hunting (see also Rick et al 2012b). As scholars in Australia, the Caribbean, and California noted, some island fauna survived millennia of huntergatherer occupations, but went on to be decimated during the historic period (see Ainis and Vellanoweth 2012;Fitzpatrick and Keegan 2007;Walshe 2014).…”
Section: Contributions To Biogeography and Ecologymentioning
confidence: 87%